A comparative study of Rh2-catalyzed intermolecular nitrene transfer reactions: mechanism and chemoselectivity. Issue 11 (27th April 2022) - Wang, Juping; Zheng, Kangcheng; Xiao, Rongxing; Qian, Li; Lin, Zijie
Abstract : The intermolecular catalytic mechanisms using Rh2 (esp)2 and Rh2 (OAc)4 are analogous and their large difference in aziridination-to-amination chemoselectivity stems from the steric effect. Abstract : The mechanism and chemoselectivity of Rh2 -catalyzed intermolecular nitrene transfer reactions of carvone have been investigated using the M06L method. By comparing Rh2 (esp)2 vs. Rh2 (OAc)4 catalysis, the origin of aziridination-to-amination chemoselectivity is revealed. The stepwise radical pathways are preferred for aziridination and amination by the two Rh2 catalysts. However, the Rh2 (esp)2 and Rh2 (OAc)4 catalysts have a large difference in their aziridination-to-amination chemoselectivity, and this difference stems from the steric effect. Exclusive aziridines are obtained by Rh2 (OAc)4 because the π-bond is more electron-rich and has a lower bond dissociation energy (BDE) compared to that of the σC–H bond. However, for Rh2 (esp)2 catalysis, the disadvantage from the larger steric congestion compensates for the advantage from the lower BDE of the π-bond in aziridination, leading to a similar yield of aziridine and amine. The stepwise mechanisms and ligand-dependent chemoselectivities of the intermolecular nitrene transfer reactions are strikingly different from those of the intramolecular ones. This work offers valuable information for the further development of highly efficient and selective catalysts, which can be applied to intermolecular nitrene transfer reactions.